Cerebral perfusion correlates of depressed mood. - Ebmeier, K; Cavanagh, J; Moffoot, A; Glabus, M; O'Carroll, R; Goodwin, G (1997)
BACKGROUND: The spontaneous diurnal variation of mood and other symptoms provides a substrate for the examination of the relationship between symptoms and regional brain activation in depression. METHOD: Twenty unipolar depressed patients with diurnal variation of mood were examined at 8 a.m. and 8 p.m. with neuropsychological measures, clinical ratings and single photon emission tomography (SPET). Brain perfusion maps were spatially transformed into standard stereotactic space and compared pixel-by-pixel. A parametric (correlational) analysis was used to examine the relationship between symptom severity and brain perfusion, both between and within subjects. RESULTS: Global depression severity and an independent 'vital' depression factor were associated in subjects with increased perfusion in cingulate and other paralimbic areas. In addition there was a probable association between an increase in an anxious-depression factor and reduced frontal neocortical perfusion. CONCLUSIONS: Depressive symptom changes are associated with metabolic changes in the cingulate gyrus and associated paralimbic structures.